An investigation of a framework for the implementation of service management in the information and communication technology sector - Benyon, Robert Victor (Rhodes University, Faculty of Commerce, Department of Information Systems, 2006)
Service Management (SM) is an integrated, cyclical and collaborative approach to the management of service requirements and levels. It involves the definition of client expectations, the satisfying of those expectations and the perpetual refining of the business agreement (Sturm 2001). SM in the ICT sector is a comprehensive process that extends beyond the development of Service Agreements (SAs). A number of identifiable steps constitute the progressive implementation of a managed services environment, the key components of which are a readiness to provide services, the accurate elicitation, management and satisfying of client requirements and the continual improvements to the business relationship. Unfortunately, a number of SM initiatives fail. These failures can be attributed to a lack of SM understanding, the absence of a fully implemented SM strategy, poor communication and people issues. This research describes an investigation of SM implementation. A number of recognised frameworks are explored and critically analysed. The common strengths of these frameworks and the results of an exploratory pilot study are used to construct an SM implementation framework. This framework is then tested empirically by means of an online survey, and revised in the light of the results of this survey. The framework comprises two distinct phases, namely a Foundation phase and a Managed Services phase. The Foundation phase comprises 8 critical preparatory activities that take a service provider to state of readiness to provide and manage ICT services. The Managed Services phase comprises 5 key cyclical steps for the management of ICT services, including Planning, Analysis, Design, Implementation and Review.
Keywords: Support services (Management); Service industries -- Management; Information technology -- Management; Management information systems; Communication in management